Evaluación de la metodología de la enseñanza por área formativa de la carrera de enfermería. Diseño y rediseño. 2021 - Egas Quintanilla, Dayana (2022)
The present investigation entitled “EVALUATION OF THE TEACHING METHODOLOGY BY TRAINING AREA OF THE NURSING CAREER. DESIGN AND REDESIGN. 2021" aims to "Determine the teaching methodologies by training area used in the Nursing Career of the State University of Bolívar, in the design and redesign curriculum during the year 2021". Being developed under a quantitative approach, explanatory design, descriptive scope; considering as a population sample 300 students and 25 teachers of the Nursing Career; using the questionnaire as an instrument for collecting information and the survey as a technique. Descriptive statistics were used in data processing, obtaining as a result that: 76% of the students consider that group activities are developed; 70% believe that some teachers use ICTs in classes; 66% consider that they have participated in evaluations where skills and abilities are rated. 76% of teachers consider that the objectives of the subjects are clearly structured; 81% consider that the methodologies of the curriculum are clear and feasible; 64% apply traditional methodologies; 88% apply methodologies that generate knowledge. In the redesign, 40% apply traditional methodologies at the Basic level. In conclusion: the teachers in the Basic Unit use combined methodologies, in the Professional Unit the teachers use participatory methodologies to generate knowledge and not rote, both in the Design and in the Redesign of the Curriculum Mesh and in the Degree, all use rote methodologies.